Yttria-based composite ceramic crucible for smelting niobium-based alloys and preparation method thereof
By using materials such as yttrium oxide, titanium carbide, hyperbranched polycarbosilane, combined with high-energy ball milling and vacuum impregnation, the Ti3SiC2 phase is formed, which solves the problem that existing yttrium oxide-based composite ceramic crucibles are easily damaged and have a short service life under high temperatures. The problem is that excellent fracture toughness, thermal shock stability and resistance to alloy melt corrosion are achieved, which extends service life and improves the cleanliness of alloy melt.
Patent Information
- Application Number
- CN202310491779.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-05
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-05-05
AI Technical Summary
The existing yttrium oxide-based composite ceramic crucibles are prone to damage at high temperatures, have short service life, and lack the ability to resist alloy melt corrosion, which affects the cleanliness of alloy melt.
Using yttrium oxide, titanium carbide, hyperbranched polycarbosilane, silicon powder and other materials, the Ti3SiC2 phase is formed through high-energy ball milling, cold isostatic molding, vacuum induction sintering, vacuum impregnation and silicon permeation processes, and the fracture toughness of the crucible is improved and Thermal shock stability and enhance the resistance to alloy melt corrosion.
The fracture toughness, thermal shock stability and resistance to alloy melt corrosion of yttrium-based composite ceramic crucibles for niobium-based alloy smelting have been significantly improved, and the service life is extended, and the cleanliness of the alloy melt is improved.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of yttria-based multiphase ceramic crucibles, and specifically relates to a yttria-based multiphase ceramic crucible for niobium-based alloy smelting and a preparation method thereof. Technical Background
[0002] Niobium-based alloys are widely used in high-temperature hot end parts of engines and gas turbines in the aviation and aerospace industries due to their good oxidation resistance, fatigue resistance, corrosion resistance and excellent high-temperature strength. Vacuum induction melting (VIM) is widely used in the preparation of niobium-based alloys. Crucibles are important components of the VIM method, and their working performance has a significant impact on the structure and properties of the smelted alloys. Yttrium oxide (Y2O3) has alloy corrosion resistance and high-temperature stability that other oxide materials cannot match, and is an ideal crucible material for niobium-based alloy melting.
[0003] The patented technology of "A micro-nano dual-scale yttrium oxide crucible" (202110705845.0) is that the crucible has two layers, the outer layer is micron-grade yttrium oxide, and the inner layer is nano-grade yttrium oxide, which is prepared by the method of slip injection molding. The particle sizes of the yttrium oxide powders in the inner and outer layers of this crucible are very different, and it is very easy to be damaged due to uneven distribution of thermal stress at high temperatures. In addition, this crucible is prepared by slip injection molding. The ceramic additives and defoaming agents used in this method will introduce impurity elements, which will cause the crucible to react more easily with the alloy melt and reduce the service life of the crucible.
[0004] "A low-temperature sintered yttrium oxide ceramic crucible" (202110388155.7) patented technology, the crucible uses magnesium oxide and titanium oxide powder as sintering aids, which are directly mixed with yttrium oxide powder and pressed and sintered. This crucible has an extremely high density (98% to 99.5% of the theoretical density), but this will significantly reduce the thermal shock stability of the crucible. In addition, the adhesive used in this crucible is mostly organic polymers, and the open pores produced during the sintering process will have a negative impact on the crucible's ability to resist alloy melt erosion.
[0005] The patented technology of "A fused yttrium oxide ceramic crucible for titanium alloy molten casting" (201610593898.7) is mainly composed of high-purity yttrium oxide particles (purity 99.999%) and ZrO2 prepared by the electric melting method, supplemented by ethylene alcohol water-soluble binder and sintered at 1750°C. The yttrium oxide particles in this crucible have a wide gradation, which improves the thermal shock stability of the crucible to a certain extent, but it also makes it difficult for the yttrium oxide particles to be tightly stacked, resulting in a decrease in the ability to resist erosion by the alloy melt. In addition, the ZrO2 in the component will undergo volume changes due to phase change at high temperatures, which will affect the volume stability of the crucible during the sintering process, and ZrO2 is easy to react with elements such as Ti and Ni in the alloy to generate impurities such as α-Ti(Zr,O) and Zr2Ni, resulting in a decrease in the local volume stability of the crucible and a reduction in the cleanliness of the alloy melt. Summary of the invention
[0006] The present invention aims to overcome the defects in the prior art and aims to provide a yttria-based composite ceramic crucible for niobium-based alloy smelting and a preparation method thereof. The prepared yttria-based composite ceramic crucible for niobium-based alloy smelting has excellent fracture toughness, good thermal shock stability, excellent resistance to alloy melt erosion, long service life and high cleanliness of the alloy melt.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] 1) Yttrium oxide powder and titanium carbide powder are mixed in a mass ratio of 1:0.11-0.43, ball milled for 24-48 hours using a high-energy ball mill, and then dried at 100-120° C. for 24-48 hours to obtain a composite powder.
[0009] 2) The composite powder is subjected to cold isostatic pressing to obtain a crucible blank; the cold isostatic pressing is performed at a pressure of 200 to 250 MPa for 3 to 5 minutes.
[0010] 3) vacuum induction sintering the crucible blank to obtain a crucible base; the vacuum induction sintering is carried out at a vacuum degree of 10 -3 ~10 -2 MPa and sintering at 1400-1600℃ for 0.5-1.5h.
[0011] 4) drying the crucible substrate at room temperature for 12 to 24 hours, and then placing it in hyperbranched polycarbosilane at a vacuum degree of 10 -3 ~10 -2 MPa and a pressure of 5 to 8 MPa, maintaining the pressure for 4 to 8 hours; then curing at 120 to 150° C. and an argon atmosphere for 6 to 8 hours, and high-temperature pyrolysis at 1200 to 1400° C. and an argon atmosphere for 6 to 8 hours to obtain a pretreated crucible substrate.
[0012] 5) embedding the pretreated crucible substrate in silicon powder-calcium chloride composite powder and sintering in a vacuum induction furnace at a vacuum degree of 10 -3 ~10 -2 MPa and 1700-1900°C for 0.5-1.5h to obtain a yttrium oxide-based composite ceramic crucible for smelting niobium-based alloys.
[0013] The silicon powder-calcium chloride composite powder is a mixture of silicon powder and calcium chloride powder, and the mass ratio of the silicon powder to the calcium chloride powder is 1:0.01-0.11; wherein: the average particle size of the silicon powder is 100nm, and the purity is 99.9-99.99%; the average particle size of the calcium chloride powder is 100nm, and the purity is 99.9-99.99%.
[0014] The yttrium oxide powder has an average particle size of 10 μm and a purity of 99.9-99.99%.
[0015] The titanium carbide powder has an average particle size of 1 μm and a purity of 99.9-99.99%.
[0016] The high-energy ball mill has a rotation speed of 600-800 rpm, a ball milling jar made of agate, a ball milling medium made of anhydrous ethanol, a grinding ball made of zirconium oxide, and a mass ratio of grinding balls to raw materials of 1:0.100-0.125.
[0017] The hyperbranched polycarbosilane has a viscosity of 30 to 100 mPa·s and a number average molecular weight of 1000 to 2000.
[0018] Due to the adoption of the above technical solution, the present invention has the following positive effects compared with the prior art:
[0019] 1. Since the present invention uses yttrium oxide, titanium carbide, hyperbranched polycarbosilane, silicon powder and the like as main raw materials, through the effective combination of vacuum impregnation, induction sintering, vacuum siliconization and other processes, the Ti3SiC2 phase is formed in situ between the yttrium oxide particles and in the pores in the crucible material structure. The Ti3SiC2 grains have a special nano-layered structure, which ensures that the cracks only deflect between the layers when the crucible is impacted by external forces; at the same time, since the Ti3SiC2 grain orientation is anisotropic, under the action of multiple stresses generated by external force impact, basal slip and transgranular fracture occur, so that the external force is dissipated in various forms. Therefore, the prepared yttrium oxide-based composite ceramic crucible for niobium-based alloy smelting has excellent fracture toughness.
[0020] 2. Since the present invention uses hyperbranched polycarbosilane as a precursor, combined with vacuum impregnation and siliconization processes, the Ti3SiC2 phase is evenly dispersed in the structure and is tightly combined with yttrium oxide through the intergranular phase Y2SiO5; in addition, the Ti3SiC2 phase can be pinned at the yttrium oxide grain boundary, hindering grain boundary migration and grain movement and inhibiting grain growth, thus refining the grains and limiting the transmission of thermal stress to the inside of the crucible. Therefore, the prepared yttrium oxide-based composite ceramic crucible for niobium-based alloy smelting has good thermal shock stability.
[0021] 3. Since the Ti3SiC2 phase generated in situ in the present invention can be pinned at the grain boundary, the diffusion and erosion of the alloy melt at the grain boundary are inhibited. In addition, the Ti3SiC2 phase itself has poor wettability with the niobium-based alloy, and in the vacuum siliconizing process, calcium chloride is used to locally form droplets to form a liquid medium, which increases the reaction rate, thereby increasing the yield of the Ti3SiC2 phase. Therefore, the increase in the Ti3SiC2 phase content in the crucible effectively improves the crucible material's resistance to alloy erosion; in addition, the crucible has a low apparent porosity, which can effectively reduce the penetration of the alloy melt at the pores. Therefore, the prepared yttria-based composite ceramic crucible for niobium-based alloy smelting has excellent resistance to alloy melt erosion.
[0022] 4. Since the present invention has excellent fracture toughness, good thermal shock stability and excellent resistance to alloy melt erosion, it can not only significantly improve the service life of the prepared yttria-based composite ceramic crucible for niobium-based alloy smelting, but also significantly improve the cleanliness of the alloy melt.
[0023] The yttria-based composite ceramic crucible for smelting niobium-based alloys prepared by the present invention has been tested to have a thermal shock cycle of 18 to 25 times and a fracture toughness of 2.35 to 3.92 MPa·m 1 / 2 ; No corrosion reaction layer between the crucible surface and the melt was observed; the apparent porosity was 0.16-0.83%; the relative density was 97.66-99.45%; and the compressive strength at room temperature was 285.44-311.68 MPa.
[0024] Therefore, the yttria-based composite ceramic crucible for niobium-based alloy smelting prepared by the present invention not only has excellent fracture toughness, good thermal shock stability and excellent resistance to alloy melt erosion, but also has a long service life and high cleanliness of the alloy melt. DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with specific implementation modes, but is not intended to limit the protection scope thereof.
[0026] A yttria-based composite ceramic crucible for smelting niobium-based alloys and a preparation method thereof. The preparation method described in this specific embodiment is:
[0027] 1) Yttrium oxide powder and titanium carbide powder are mixed in a mass ratio of 1:0.11-0.43, ball milled for 24-48 hours using a high-energy ball mill, and then dried at 100-120° C. for 24-48 hours to obtain a composite powder.
[0028] 2) The composite powder is subjected to cold isostatic pressing to obtain a crucible blank; the cold isostatic pressing is performed at a pressure of 200 to 250 MPa for 3 to 5 minutes.
[0029] 3) vacuum induction sintering the crucible blank to obtain a crucible base; the vacuum induction sintering is carried out at a vacuum degree of 10 -3 ~10 -2 MPa and sintering at 1400-1600℃ for 0.5-1.5h.
[0030] 4) drying the crucible substrate at room temperature for 12 to 24 hours, and then placing it in hyperbranched polycarbosilane at a vacuum degree of 10 -3 ~10 -2 MPa and a pressure of 5 to 8 MPa, maintaining the pressure for 4 to 8 hours; then curing at 120 to 150° C. and an argon atmosphere for 6 to 8 hours, and high-temperature pyrolysis at 1200 to 1400° C. and an argon atmosphere for 6 to 8 hours to obtain a pretreated crucible substrate.
[0031] 5) embedding the pretreated crucible substrate in silicon powder-calcium chloride composite powder and sintering in a vacuum induction furnace at a vacuum degree of 10 -3 ~10 -2 MPa and 1700-1900°C for 0.5-1.5h to obtain a yttrium oxide-based composite ceramic crucible for smelting niobium-based alloys.
[0032] The silicon powder-calcium chloride composite powder is a mixture of silicon powder and calcium chloride powder, and the mass ratio of the silicon powder to the calcium chloride powder is 1:0.01-0.11; wherein: the average particle size of the silicon powder is 100nm, and the purity is 99.9-99.99%; the average particle size of the calcium chloride powder is 100nm, and the purity is 99.9-99.99%.
[0033] The yttrium oxide powder has an average particle size of 10 μm and a purity of 99.9-99.99%.
[0034] The titanium carbide powder has an average particle size of 1 μm and a purity of 99.9-99.99%.
[0035] The high-energy ball mill has a rotation speed of 600-800 rpm, a ball milling jar made of agate, a ball milling medium made of anhydrous ethanol, a grinding ball made of zirconium oxide, and a mass ratio of grinding balls to raw materials of 1:0.100-0.125.
[0036] The hyperbranched polycarbosilane has a viscosity of 30 to 100 mPa·s and a number average molecular weight of 1000 to 2000.
[0037] Example 1
[0038] A yttria-based composite ceramic crucible for smelting niobium-based alloys and a preparation method thereof. The preparation method described in this embodiment is:
[0039] 1) Yttrium oxide powder and titanium carbide powder were mixed in a mass ratio of 1:0.43, ball-milled for 48 hours using a high-energy ball mill, and then dried at 100° C. for 24 hours to obtain a composite powder.
[0040] 2) The composite powder is subjected to cold isostatic pressing to obtain a crucible blank; the cold isostatic pressing is performed at a pressure of 200 MPa for 3 minutes.
[0041] 3) vacuum induction sintering the crucible blank to obtain a crucible base; the vacuum induction sintering is carried out at a vacuum degree of 10 -2 MPa and sintered at 1400℃ for 1.0h.
[0042] 4) The crucible substrate was dried at room temperature for 12 h, and then placed in hyperbranched polycarbosilane at a vacuum degree of 10 -2 MPa and pressure of 5MPa for 4 hours; then solidify at 120°C in an argon atmosphere for 8 hours, and high-temperature pyrolysis at 1400°C in an argon atmosphere for 8 hours to obtain a pretreated crucible substrate.
[0043] 5) embedding the pretreated crucible substrate in silicon powder-calcium chloride composite powder and sintering in a vacuum induction furnace at a vacuum degree of 10 -2 MPa and 1700°C for 1.0h to obtain a yttria-based composite ceramic crucible for smelting niobium-based alloys.
[0044] The silicon powder-calcium chloride composite powder is a mixture of silicon powder and calcium chloride powder, and the mass ratio of the silicon powder to the calcium chloride powder is 1:0.01; wherein: the average particle size of the silicon powder is 100nm, and the purity is 99.9%; the average particle size of the calcium chloride powder is 100nm, and the purity is 99.9%.
[0045] The yttrium oxide powder has an average particle size of 10 μm and a purity of 99.9%.
[0046] The titanium carbide powder has an average particle size of 1 μm and a purity of 99.9%.
[0047] The high-energy ball mill has a rotation speed of 600 rpm, a ball milling jar made of agate, a ball milling medium made of anhydrous ethanol, a grinding ball made of zirconium oxide, and a mass ratio of grinding balls to raw materials of 1:0.100.
[0048] The hyperbranched polycarbosilane has a viscosity of 30 mPa·s and a number average molecular weight of 1000.
[0049] The yttria-based composite ceramic crucible for smelting niobium-based alloys prepared in this embodiment has been tested to have a thermal shock cycle of 19 times and a fracture toughness of 3.26 MPa·m 1 / 2 ; No corrosion reaction layer between the crucible surface and the melt was observed; the apparent porosity was 0.53%; the relative density was 98.35%; and the compressive strength at room temperature was 290.73MPa.
[0050] Example 2
[0051] A yttria-based composite ceramic crucible for smelting niobium-based alloys and a preparation method thereof. The preparation method described in this embodiment is:
[0052] 1) Yttrium oxide powder and titanium carbide powder were mixed in a mass ratio of 1:0.33, ball milled for 36 hours using a high-energy ball mill, and then dried at 105° C. for 36 hours to obtain a composite powder.
[0053] 2) The composite powder is subjected to cold isostatic pressing to obtain a crucible blank; the cold isostatic pressing is performed at a pressure of 220 MPa for 4 minutes.
[0054] 3) vacuum induction sintering the crucible blank to obtain a crucible base; the vacuum induction sintering is carried out at a vacuum degree of 10 -2 MPa and sintered at 1500℃ for 0.5h.
[0055] 4) drying the crucible substrate at room temperature for 18 h, and then placing it in hyperbranched polycarbosilane at a vacuum degree of 10 -2 MPa and the pressure is maintained at 6MPa for 6 hours; then, it is cured at 130°C and argon atmosphere for 7 hours, and high-temperature pyrolysis is performed at 1300°C and argon atmosphere for 7 hours to obtain a pretreated crucible substrate.
[0056] 5) embedding the pretreated crucible substrate in silicon powder-calcium chloride composite powder and sintering in a vacuum induction furnace at a vacuum degree of 10 -2 MPa and 1800°C for 0.5h to obtain a yttria-based composite ceramic crucible for smelting niobium-based alloys.
[0057] The silicon powder-calcium chloride composite powder is a mixture of silicon powder and calcium chloride powder, and the mass ratio of the silicon powder to the calcium chloride powder is 1:0.05; wherein: the average particle size of the silicon powder is 100nm, and the purity is 99.93%; the average particle size of the calcium chloride powder is 100nm, and the purity is 99.95%.
[0058] The yttrium oxide powder has an average particle size of 10 μm and a purity of 99.95%.
[0059] The titanium carbide powder has an average particle size of 1 μm and a purity of 99.95%.
[0060] The high-energy ball mill has a rotation speed of 700 rpm, a ball milling jar made of agate, a ball milling medium made of anhydrous ethanol, a grinding ball made of zirconium oxide, and a mass ratio of grinding balls to raw materials of 1:0.105.
[0061] The hyperbranched polycarbosilane has a viscosity of 50 mPa·s and a number average molecular weight of 1500.
[0062] The yttria-based composite ceramic crucible material for niobium-based alloy smelting prepared in this embodiment has been tested: the number of thermal shock cycles is up to 25 times; the fracture toughness is 3.92 MPa·m 1 / 2 ; No corrosion reaction layer between the crucible surface and the melt was observed; the apparent porosity was 0.83%; the relative density was 97.66%; and the compressive strength at room temperature was 311.68MPa.
[0063] Example 3
[0064] A yttria-based composite ceramic crucible for smelting niobium-based alloys and a preparation method thereof. The preparation method described in this embodiment is:
[0065] 1) Yttrium oxide powder and titanium carbide powder were mixed in a mass ratio of 1:0.22, ball milled for 24 hours using a high-energy ball mill, and then dried at 110° C. for 24 hours to obtain a composite powder.
[0066] 2) The composite powder is subjected to cold isostatic pressing to obtain a crucible blank; the cold isostatic pressing is performed at a pressure of 240 MPa for 4 minutes.
[0067] 3) vacuum induction sintering the crucible blank to obtain a crucible base; the vacuum induction sintering is carried out at a vacuum degree of 10 -3 MPa and sintered at 1550℃ for 1.0h.
[0068] 4) drying the crucible substrate at room temperature for 18 h, and then placing it in hyperbranched polycarbosilane at a vacuum degree of 10 -3MPa and the pressure is 7MPa, and the pressure is maintained for 7 hours; then, it is cured at 140°C and an argon atmosphere for 6 hours, and is high-temperature pyrolyzed at 1200°C and an argon atmosphere for 6 hours to obtain a pretreated crucible substrate.
[0069] 5) embedding the pretreated crucible substrate in silicon powder-calcium chloride composite powder and sintering in a vacuum induction furnace at a vacuum degree of 10 -3 MPa and 1900°C for 1.0h to obtain a yttria-based composite ceramic crucible for smelting niobium-based alloys.
[0070] The silicon powder-calcium chloride composite powder is a mixture of silicon powder and calcium chloride powder, and the mass ratio of the silicon powder to the calcium chloride powder is 1:0.08; wherein: the average particle size of the silicon powder is 100nm, and the purity is 99.95%; the average particle size of the calcium chloride powder is 100nm, and the purity is 99.97%.
[0071] The yttrium oxide powder has an average particle size of 10 μm and a purity of 99.97%.
[0072] The titanium carbide powder has an average particle size of 1 μm and a purity of 99.97%.
[0073] The high-energy ball mill has a rotation speed of 750 rpm, a ball milling jar made of agate, a ball milling medium made of anhydrous ethanol, a grinding ball made of zirconium oxide, and a mass ratio of grinding balls to raw materials of 1:0.115.
[0074] The hyperbranched polycarbosilane has a viscosity of 80 mPa·s and a number average molecular weight of 1800.
[0075] The yttria-based composite ceramic crucible material for niobium-based alloy smelting prepared in this embodiment has been tested: the number of thermal shock cycles is up to 22 times; the fracture toughness is 3.41 MPa·m 1 / 2 ; No corrosion reaction layer between the crucible surface and the melt was observed; the apparent porosity was 0.47%; the relative density was 98.83%; and the compressive strength at room temperature was 289.72MPa.
[0076] Example 4
[0077] A yttria-based composite ceramic crucible for smelting niobium-based alloys and a preparation method thereof. The preparation method described in this embodiment is:
[0078] 1) Yttrium oxide powder and titanium carbide powder were mixed in a mass ratio of 1:0.11, ball milled for 40 hours using a high-energy ball mill, and then dried at 120° C. for 48 hours to obtain a composite powder.
[0079] 2) The composite powder is subjected to cold isostatic pressing to obtain a crucible blank; the cold isostatic pressing is performed at a pressure of 250 MPa for 5 minutes.
[0080] 3) vacuum induction sintering the crucible blank to obtain a crucible base; the vacuum induction sintering is carried out at a vacuum degree of 10 -3 MPa and sintered at 1600℃ for 1.5h.
[0081] 4) The crucible substrate was dried at room temperature for 24 h, and then placed in a hyperbranched polycarbosilane at a vacuum degree of 10 -3 MPa and pressure of 8MPa for 8h; then solidify at 150°C in an argon atmosphere for 8h, and high-temperature pyrolysis at 1250°C in an argon atmosphere for 6.5h to obtain a pretreated crucible substrate.
[0082] 5) embedding the pretreated crucible substrate in silicon powder-calcium chloride composite powder and sintering in a vacuum induction furnace at a vacuum degree of 10 -3 MPa and 1850°C for 1.5h to obtain a yttria-based composite ceramic crucible for smelting niobium-based alloys.
[0083] The silicon powder-calcium chloride composite powder is a mixture of silicon powder and calcium chloride powder, and the mass ratio of the silicon powder to the calcium chloride powder is 1:0.11, wherein: the average particle size of the silicon powder is 100nm, and the purity is 99.99%; the average particle size of the calcium chloride powder is 100nm, and the purity is 99.99%.
[0084] The yttrium oxide powder has an average particle size of 10 μm and a purity of 99.99%.
[0085] The titanium carbide powder has an average particle size of 1 μm and a purity of 99.99%.
[0086] The high-energy ball mill has a rotation speed of 800 rpm, a ball milling jar made of agate, a ball milling medium made of anhydrous ethanol, a grinding ball made of zirconium oxide, and a mass ratio of grinding balls to raw materials of 1:0.125.
[0087] The hyperbranched polycarbosilane has a viscosity of 100 mPa·s and a number average molecular weight of 2000.
[0088] The yttria-based composite ceramic crucible for smelting niobium-based alloys prepared in this embodiment has been tested to have a thermal shock cycle of 18 times and a fracture toughness of 2.35 MPa·m 1 / 2 ; No corrosion reaction layer between the crucible surface and the melt was observed; the apparent porosity was 0.16%; the relative density was 99.45%; and the compressive strength at room temperature was 285.44MPa.
[0089] Compared with the prior art, this specific implementation has the following positive effects:
[0090] 1. Since this specific implementation method uses yttrium oxide, titanium carbide, hyperbranched polycarbosilane, silicon powder and the like as the main raw materials, through the effective combination of vacuum impregnation, induction sintering, vacuum siliconization and other processes, the Ti3SiC2 phase is formed in situ between the yttrium oxide particles and in the pores in the crucible material structure. The Ti3SiC2 grains have a special nano-layered structure, which ensures that the cracks only deflect between the layers when the crucible is impacted by external forces; at the same time, since the Ti3SiC2 grain orientation is anisotropic, under the action of multiple stresses generated by external force impact, basal slip and transgranular fracture occur, so that the external force is dissipated in various forms. Therefore, the yttrium oxide-based composite ceramic crucible for niobium-based alloy smelting prepared in this specific implementation method has excellent fracture toughness.
[0091] 2. Since the present embodiment uses hyperbranched polycarbosilane as a precursor, and cooperates with vacuum impregnation and siliconization processes, the Ti3SiC2 phase is evenly dispersed in the structure and is tightly combined with yttrium oxide through the intergranular phase Y2SiO5; in addition, the Ti3SiC2 phase can be pinned at the yttrium oxide grain boundary, hindering grain boundary migration and grain movement and inhibiting grain growth, thus refining the grains and limiting the transmission of thermal stress to the inside of the crucible. Therefore, the prepared yttrium oxide-based composite ceramic crucible for niobium-based alloy smelting has good thermal shock stability.
[0092] 3. Since the Ti3SiC2 phase generated in situ in this specific embodiment can be pinned at the grain boundary, the diffusion and erosion of the alloy melt at the grain boundary are inhibited. In addition, the Ti3SiC2 phase itself has poor wettability with the niobium-based alloy, and in the vacuum siliconizing process, calcium chloride is used to locally form droplets to form a liquid medium, which increases the reaction rate and thus increases the yield of the Ti3SiC2 phase. Therefore, the increase in the Ti3SiC2 phase content in the crucible effectively improves the resistance of the crucible material to alloy erosion; in addition, the crucible has a low apparent porosity, which can effectively reduce the penetration of the alloy melt at the pores. Therefore, the yttrium oxide-based composite ceramic crucible for niobium-based alloy smelting prepared in this specific embodiment has excellent resistance to alloy melt erosion.
[0093] 4. Since this specific implementation has excellent fracture toughness, good thermal shock stability and excellent resistance to alloy melt corrosion, it can not only significantly improve the service life of the prepared yttria-based composite ceramic crucible for niobium-based alloy smelting, but also significantly improve the cleanliness of the alloy melt.
[0094] The yttria-based composite ceramic crucible for smelting niobium-based alloys prepared in this specific embodiment has been tested to have a thermal shock cycle of 18 to 25 times and a fracture toughness of 2.35 to 3.92 MPa·m 1 / 2; No corrosion reaction layer between the crucible surface and the melt was observed; the apparent porosity was 0.16-0.83%; the relative density was 97.66-99.45%; and the compressive strength at room temperature was 285.44-311.68 MPa.
[0095] Therefore, the yttria-based composite ceramic crucible for niobium-based alloy smelting prepared in this specific embodiment not only has excellent fracture toughness, good thermal shock stability and excellent resistance to alloy melt erosion, but also has a long service life and high cleanliness of the alloy melt.
Claims
1. A method for preparing a yttria-based composite ceramic crucible for smelting niobium-based alloys, characterized in that The preparation method is: 1) yttrium oxide powder and titanium carbide powder are mixed in a mass ratio of 1:0.11-0.43, ball milled in a high-energy ball mill for 24-48 hours, and then dried at 100-120° C. for 24-48 hours to obtain a composite powder; 2) performing cold isostatic pressing on the composite powder to obtain a crucible blank; The cold isostatic pressing is performed by maintaining the pressure at 200-250 MPa for 3-5 minutes; 3) vacuum induction sintering the crucible blank to obtain a crucible base; the vacuum induction sintering is carried out at a vacuum degree of 10 -3 ~10 -2 MPa and sintering at 1400-1600℃ for 0.5-1.5h; 4) drying the crucible substrate at room temperature for 12 to 24 hours, and then placing it in hyperbranched polycarbosilane at a vacuum degree of 10 -3 ~10 -2 MPa and a pressure of 5 to 8 MPa, maintaining the pressure for 4 to 8 hours; then curing at 120 to 150° C. and an argon atmosphere for 6 to 8 hours, and high-temperature pyrolysis at 1200 to 1400° C. and an argon atmosphere for 6 to 8 hours to obtain a pretreated crucible substrate; 5) embedding the pretreated crucible substrate in silicon powder-calcium chloride composite powder and sintering in a vacuum induction furnace at a vacuum degree of 10 -3 ~10 -2 MPa and 1700-1900°C for 0.5-1.5h to obtain a yttria-based composite ceramic crucible for smelting niobium-based alloys; The silicon powder-calcium chloride composite powder is a mixture of silicon powder and calcium chloride powder, and the mass ratio of the silicon powder to the calcium chloride powder is 1:0.01-0.11; wherein: the average particle size of the silicon powder is 100nm, and the purity is 99.9-99.99%; the average particle size of the calcium chloride powder is 100nm, and the purity is 99.9-99.99%.
2. The method for preparing the yttria-based composite ceramic crucible for smelting niobium-based alloys according to claim 1, characterized in that The yttrium oxide powder has an average particle size of 10 μm and a purity of 99.9-99.99%.
3. The method for preparing the yttria-based composite ceramic crucible for smelting niobium-based alloys according to claim 1, characterized in that The titanium carbide powder has an average particle size of 1 μm and a purity of 99.9-99.99%.
4. The method for preparing the yttria-based composite ceramic crucible for smelting niobium-based alloys according to claim 1, characterized in that The high-energy ball mill has a rotation speed of 600-800 rpm, a ball milling jar made of agate, a ball milling medium made of anhydrous ethanol, a grinding ball made of zirconium oxide, and a mass ratio of grinding balls to raw materials of 1:0.100-0.
125.
5. The method for preparing the yttria-based composite ceramic crucible for smelting niobium-based alloys according to claim 1, characterized in that The hyperbranched polycarbosilane has a viscosity of 30 to 100 mPa·s and a number average molecular weight of 1000 to 2000.
6. A yttria-based composite ceramic crucible for smelting niobium-based alloys, characterized in that The yttria-based composite ceramic crucible for smelting niobium-based alloys is prepared by the method for preparing a yttria-based composite ceramic crucible for smelting niobium-based alloys according to any one of claims 1 to 5.
Citation Information
Patent Citations
Electrical-melting yttrium oxide ceramic crucible for titanium alloy melting casting and preparation method of ceramic crucible
CN106116578A
Method for sintering yttrium oxide ceramic crucible at low temperature
CN112939603A
Micro / nano dual-scale yttrium oxide crucible and preparation method thereof
CN113548905A
Ceramic part and production method thereof
CN106977184A
Self-healing thermal barrier ceramic coating layer material for metal surface, and preparation method thereof
CN107119251A